2009
DOI: 10.1055/s-0029-1241851
|View full text |Cite
|
Sign up to set email alerts
|

New Mutations in the RET Protooncogene-L881V – Associated with Medullary Thyroid Carcinoma and -R770Q – in a Patient with Mixed Medullar/Follicular Thyroid Tumour

Abstract: Our clinical findings indicate that the L881V mutation may be associated with late-onset nonaggressive disease. If the germline RET R770Q variant has a causative role in the pathogenesis of the mixed medullar/follicular derived histology of the thyroid tumour in the index patient of family 1 has to be proven. The recommendations for prophylactic thyroidectomy in these mutations should be individualized depending on basal and stimulated calcitonin levels until more data are available.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 14 publications
0
9
0
Order By: Relevance
“…There is no evidence of pathogenicity of this variant in the literature; it was initially reported in a case of HSCR and later in the sister of an MTC case harbouring RET R770Q ( Ruiz-Ferrer et al . 2006 , Frank-Raue et al . 2010 ).…”
Section: Resultsmentioning
confidence: 99%
“…There is no evidence of pathogenicity of this variant in the literature; it was initially reported in a case of HSCR and later in the sister of an MTC case harbouring RET R770Q ( Ruiz-Ferrer et al . 2006 , Frank-Raue et al . 2010 ).…”
Section: Resultsmentioning
confidence: 99%
“…The histological morphology of MTC and RET mutation points also has some correlations. Frank-Raue et al [13] reported RET proto-oncogene-L881V to be associated with MTC and R770Q to be associated with mixed medullar/follicular thyroid tumor. During the review of 13 MTC cases from five unrelated families with either MEN 2A (families A, B, C, and D) or FMTC (family E), we observed that members of the same family had a 66.7–100% similarity rate in MTC cytomorphology.…”
Section: Discussionmentioning
confidence: 99%
“…A study of Frank-Raue showed level 1 mutations were diagnosed in 38.9% of families, and level 2 and 3 mutations were screened in 54.4 and 5.6% of families [19]. At the same time, some rare (codon 631) and de novo mutations (codons 292 and 881) have emerged [20,21]. Kalliopi et al [22] reported two de novo mutations (the 2458C[T mutation and the transition from I590 to G608) associated with MEN2.…”
Section: Ret Genetic Screeningmentioning
confidence: 99%